Structural Connections: Algorithms as Rituals and Rituals as Algorithms - Mark Burgin (Proceedings, 2022)
In this paper, we analyze relations between rituals and algorithms with the goal of achieving better knowledge of both phenomena as systems of control information about processes. Similarities and dissimilarities between rituals and algorithms are explicated and explored.